Carbon Isotopes (δ13C and Δ14C) in Shell Carbonate, Conchiolin, and Soft Tissues in Eastern Oyster (Crassostrea Virginica). Issue 4 (27th April 2018) - Hadden, Carla S; Loftis, Kathy M; Cherkinsky, Alexander
Abstract: Biogeochemical analyses of eastern oysters ( Crassostrea virginica ) are frequently included in environmental monitoring and paleoecological studies because their shells and soft tissues record environmental and dietary signals. Carbon isotopes in the mineral phase of the shell are derived from ambient bicarbonate and dissolved inorganic carbon (DIC), while organic carbon present in soft tissue is of dietary origin. Mineral-bound organic matter within the carbonate shell matrix ("conchiolin") is studied less frequently. The purpose of this study was to compare carbon isotope composition (δ 13 C and Δ 14 C) of conchiolin to those of shell carbonates and soft tissues in eastern oysters and assess the extent to which conchiolin can provide insight into paleoecological records. Eleven oyster specimens were live-collected from Apalachicola Bay, USA, as well as a set of environmental samples (water, sediment, and terrestrial plants). Overall, the δ 13 C values in all studied oyster tissue types record environmental signals related to carbon sources, with conchiolin being enriched in 13 C by an average of 2.3‰ relative to bulk soft tissues. Δ 14 C values in oyster shell carbonates generally reflect the marine versus riverine source of DIC, while conchiolin Δ 14 C values are impacted by variable relative contributions of young and old organic matter. Environmental samples indicate a significantly large difference in Δ 14 C among sources, from –127‰ in particulate organic matter to approximately +15‰ in DIC. Conchiolin is significantly depleted in 14 C relative to other tissue types, by as much as 56.6‰, posing a major obstacle to the use of conchiolin as an alternative material for radiocarbon dating.